Triangular segmentation criterion for DT mesh based video coding - GUO Da-bo1; LU Zhao-yang1; JIAO Wei-dong1; HU Xing-xing1 (Tongxin xuebao)
Based on the analysis of the deficiency of two previous Delaunay triangular mesh segmentation criterions—minimize difference of gray and minimize variance of gray, a new triangular mesh criterion, minimize sum of squared difference of gray, was proposed. The new segmentation was more rational and efficient so that the coding performance on it was improved obviously than before. Furthermore, a new hybrid coding scheme was also proposed under the criterion with transformation coding for intra frame and mesh-based motion estimation for inter frame, which could be applied in video sequence with complex motion and background. The restriction that mesh model based coding was only applicable in video conference applications was broken. Experimental result shows that the proposed scheme has a better performance than H.263 in applications with complex motion and background.